2022
DOI: 10.1063/5.0078457
|View full text |Cite
|
Sign up to set email alerts
|

Electron–phonon effects on the photoacoustic response of gold core–silica shell nanoparticles: From the linear regime to nanocavitation

Abstract: Coating gold nanostructures with a silica shell has been long considered for biomedical applications, including photoacoustic imaging. Recent experimental and modeling investigations reported contradicting results concerning the effect of coating on the photoacoustic response of gold nanostructures. Enhanced photoacoustic response is generally attributed to facilitated heat transfer at the gold/silica/water system. Here, we examine the photoacoustic response of gold core–silica shell nanoparticles immersed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Such an effect has been explained by taking into account the low interfacial thermal resistance between the Au core and the surrounding solvent in the presence of the silica shell, which allows fast heat transfer in the environment from the plasmonic NPs through the interface [ 24 , 26 ]. More recently, a theoretical investigation on Au–silica core-shell nanostructures, carried out to understand the impact of their structures in the enhanced response expected in PAI application, has concluded that direct electron–phonon coupling through the interface may provide another channel for heat to flow across the metal-dielectric interface, resulting in enhanced thermal transport at metal–nonmetal interfaces when such electron–phonon conductance is present [ 27 , 28 ]. Indeed, a deep understanding of the types of phenomena involved in the light-to-thermal energy conversion and heat transfer enhancement is strongly related to the nanostructure’s properties, including the core and shell geometry, and laser pulse duration.…”
Section: Introductionmentioning
confidence: 99%
“…Such an effect has been explained by taking into account the low interfacial thermal resistance between the Au core and the surrounding solvent in the presence of the silica shell, which allows fast heat transfer in the environment from the plasmonic NPs through the interface [ 24 , 26 ]. More recently, a theoretical investigation on Au–silica core-shell nanostructures, carried out to understand the impact of their structures in the enhanced response expected in PAI application, has concluded that direct electron–phonon coupling through the interface may provide another channel for heat to flow across the metal-dielectric interface, resulting in enhanced thermal transport at metal–nonmetal interfaces when such electron–phonon conductance is present [ 27 , 28 ]. Indeed, a deep understanding of the types of phenomena involved in the light-to-thermal energy conversion and heat transfer enhancement is strongly related to the nanostructure’s properties, including the core and shell geometry, and laser pulse duration.…”
Section: Introductionmentioning
confidence: 99%
“…The heat transfer across two materials will lead to a temperature discontinuity at the interface that is characterized by interface thermal conductance (ITC, h ). The silica-water ITC ( h sw , 150 MW m -2 K -1 ) 43 has been reported to be on the same level as ones for the gold-water interface ( h pw , 105 MW m -2 K -1 ) 44 and gold-silica interface ( h ps , 141 MW m -2 K -1 ). 26 However, a recent study suggested that the silica-water interface has thermal conductance more than 10 times higher ( h sw , 2300 MW m -2 K -1 ) than that of gold-water or gold-silica interfaces due to favorable hydrogen bonding effects.…”
Section: Resultsmentioning
confidence: 69%
“…The second channel allows energy to be directly deposited to silica phonons through the electron-phonon ( e-ph ) coupling on the gold-silica interface (Figure 3A). However, the effect of the additional e-ph heat transfer channel on PA signal generation under ns pulse laser is negligible below the threshold fluence for cavitation, 43 so it can also be neglected for ns laser excitation. For the bare AuNP, the energy is only transported from gold phonon to water phonons through the phonon-phonon interaction at the AuNP-water interface (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation